Effect of Ibuprofen Versus Acetaminophen on Postpartum Hypertension in Preeclampsia With Severe Features: A Double-masked, Randomized Controlled Trial. Issue 1 (March 2019) - Blue, N.R.; Murray-Krezan, C.; Drake-Lavelle, S.; Weinberg, D.; Holbrook, B.D.; Katukuri, V.R.; Leeman, L.; Mozurkewich, E.L.
Abstract : ( Am J Obstet Gynecol . 2018;218:616.e1–e8) Hypertensive disorders of pregnancy contribute to maternal morbidity and mortality. Women with hypertension are at increased risk for cesarean delivery. The American College of Obstetricians and Gynecologists suggests avoiding the use of nonsteroidal antiinflammatory drugs (NSAIDS) in women with preeclampsia as they have been shown to increase blood pressure in nonpregnant adults. The purpose of this study was to evaluate the effect of ibuprofen compared with acetminophen on blood pressure control in the postpartum period in women diagnosed with preeclampsia with severe features. They hypothesized that NSAIDs would adversely affect postpartum blood pressure control in women with preeclampsia with severe features.